2017
DOI: 10.1021/acs.jafc.6b05832
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate Reduces Scavenger Receptor A Expression and Foam Cell Formation in Human Macrophages

Abstract: Foam cells are formed when macrophages imbibe low-density lipoprotein (LDL) through scavenger receptors. Here we examined how epigallocatechin-3-gallate (EGCG) influences foam cell formation. We found that EGCG dose-dependently reduced oxidized LDL (oxLDL) uptake in THP-1 (10 μM, 20.0 ± 0.50, p < 0.05) and primary macrophages (134.6 ± 15.6, p < 0.05) and reduced intracellular cholesterol content in these cells, respectively (10 μM, 32.6 ± 0.14, p < 0.05; 31.7 ± 1.26, p < 0.05). EGCG treatment decreased scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The formation of foam cells induced by OxLDL is a well‐accepted model as it stimulates the growth of macrophages, upregulated the expression of scavenger receptors such as SR‐A1, SR‐B1, LOX‐1, CD‐36, and CD‐68 . In agreement with our results, a previous study demonstrated that treatment with EGCG reduced the OxLDL uptake by macrophages and prevented the formation of foam cells through the downregulated the expression of SR‐A1 scavenger receptor …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The formation of foam cells induced by OxLDL is a well‐accepted model as it stimulates the growth of macrophages, upregulated the expression of scavenger receptors such as SR‐A1, SR‐B1, LOX‐1, CD‐36, and CD‐68 . In agreement with our results, a previous study demonstrated that treatment with EGCG reduced the OxLDL uptake by macrophages and prevented the formation of foam cells through the downregulated the expression of SR‐A1 scavenger receptor …”
Section: Discussionsupporting
confidence: 92%
“…18 In agreement with our results, a previous study demonstrated that treatment with EGCG reduced the OxLDL uptake by macrophages and prevented the formation of foam cells through the downregulated the expression of SR-A1 scavenger receptor. 5 A previous study on C57BL/6 mice fed with high-fat diet showed reduced autophagy through attenuation of autophagic/lysosomal compartment, impaired lysosomal acidification, and hydrolase activity due to excessive chronic lipid accumulation. 19 In addition to this, OxLDL mediated inhibition of foam cell autophagy upregulated the expression of p62 which leads to an autophagy-deficient condition.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In macrophage cell lines, catechins also mediate suppression of expression of metalloproteinase-9 (MMP-9), monocyte chemoattractant protein-1 MCP-1, and Toll-like receptor 4 (TLR4), which have a major role in atherosclerosis [79]. Moreover, in macrophages, epigallocatechin-3-gallate (EGCG) suppresses oxLDL uptake and foam cell formation [80]. In ApoE -/mice, catechin consumption has been associated with reduced susceptibility of LDL to oxidation and aggregation and thus to the reduced atherosclerotic lesion area [81].…”
Section: Flavonoidsmentioning
confidence: 99%